"Where is the love?" Topics and prosocial behavior in German popular music lyrics from 1954 to 2014. (December 2019) - Ruth, Nicolas
Many content analyses have investigated the content of popular music, but as yet no one has looked for references to prosocial behavior in the lyrics. There are no quantitative content analyses of prosocial content in popular music, although we know that many musicians are concerned with social engagement, the environment, equal rights, and many other prosocial behaviors. To investigate which topics are the most prevalent in popular music lyrics and how frequently these refer to prosocial behavior, a content analysis was performed on 588 songs appearing in the German yearly charts from 1954 to 2014. The major interest of songwriters seems to be love, which was found in 57% of the songs; this was the most common topic found. References to prosocial behavior were found in 3.74% of the songs. Prosocial behavior usually appeared in songs dealing with social or political topics.